Computer-aided determination of the effective diffusion coefficient of a gas diffusion layer for polymer electrolyte fuel cells - Masahide Inagaki; Wataru Yoshimune; Satoru Kato (Chemical Engineering Journal Advances, 2023)
Accurate measurement of the gas diffusivity in a gas diffusion layer (GDL) for polymer electrolyte fuel cells (PEFCs) is extremely important in order to improve the performance of PEFCs and design fuel cell stacks. In the present study, in order to improve the accuracy in the determination of the gas diffusivity when uisng the simple and inexpensive method newly proposed by Yoshimune (2022), which uses an infrared absorption carbon dioxide sensor, three-dimensional (3D) simulations reproducing the experiments are performed. The results reveal that the gas transport resistance of the measurement apparatus is not small (approximately seven times higher than that of a commercial carbon paper (TGP-H060, Toray)), and the 3D simulation, which considers the resistance, reduces the error in the effective diffusion coefficient of the GDL by 25%. The effective diffusion coefficient for a new sample can be determined using the simulation results already obtained, when the apparatus is unchanged. In addition, a new one-dimensional (1D) model extended from the simple 1D model presented in Yoshimune (2022) is proposed. Since the extended model incorporates the gas transport resistance of the apparatus and dispenses with the generation of computational grids and the use of an expensive computer needed in conducting 3D simulations, this model enables us to obtain the accurate effective diffusion coefficient of a GDL with ease even when using a measurement apparatus with different sizes.